Forest typology of broadleaf forests from Sierra Maestra, Eastern Cuba - Reyes, Orlando Joel (Lazaroa, 2016)
A phytosociological study of the forests from Sierra Maestra is conducted, following the methodology of the Zurich- Montpelier School. They are transformed into a forest typology using the standards of the Institute of Agro-Forestry Research. In general, 35 types and/or subtypes are presented. From this group, the most abundant ones belong to semi-deciduous microphyll forest, followed by those from mangroves and mountain rainforest, respectively. Silvicultural treatments are needed; among them, the protection forests are those found above 800 m asl and mangroves.